2016
DOI: 10.1108/jes-07-2014-0115
|View full text |Cite
|
Sign up to set email alerts
|

Voter reaction to government incompetence and corruption related to the 1999 earthquakes in Turkey

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Most of the aggregate-level studies have found that incumbent leaders or parties get punished for disasters, even those over which they could have had no control (Achen and Bartels 2012), unless they provide postdisaster assistance, in which case they tend to be rewarded (Akarca and Tansel 2016; Cole, Healy, and Werker 2012; Gaspar and Reeves 2011; Healy and Malhotra 2009, 2010). A few studies have focused on the duration of electoral effects.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Most of the aggregate-level studies have found that incumbent leaders or parties get punished for disasters, even those over which they could have had no control (Achen and Bartels 2012), unless they provide postdisaster assistance, in which case they tend to be rewarded (Akarca and Tansel 2016; Cole, Healy, and Werker 2012; Gaspar and Reeves 2011; Healy and Malhotra 2009, 2010). A few studies have focused on the duration of electoral effects.…”
Section: Relevant Literaturementioning
confidence: 99%
“…This proposition is consistent with the so-called democratic efficiency theory and has received empirical support from Leeson and Sobel (2011) in the case of mayoral elections in New Orleans following 2005 Hurricane Katrina. 1 Akarca and Tansel (2016) provide more recent evidence, albeit for a different type of natural disaster, earthquakes. In examining the aftermath of the devastating 1999 earthquake in Turkey, Akarca and Tansel find that the Turkish electorate thereafter held accountable not only the dominant ruling party at the time of the earthquake but also other parties that were in power when the earthquake-vulnerable buildings were built.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, there was another major earthquake in Turkey in which 17,000 people died. Widespread corruption, government malfunctioning and lack of responsiveness of state institutions were blamed (Akarca & Tansel, 2016; Escaleras et al, 2007; Jalali, 2002; Lewis, 2005). In 2002, the current Turkish president, Recep Tayyip Erdoğan, came to power and promised that under his rule, things would change radically and corruption would end (Yılmaz & Soyaltın, 2014).…”
Section: Corruption In Turkey: Focus On the Construction Sector Durin...mentioning
confidence: 99%